Microeconomics - Pindyck, Robert S. (Pearson, 2005)
KEY BENEFIT: This book is well known for its coverage of modern topics (Game theory, Economics of Information, and Behavioral Economics), clarity of its writing style and graphs, and integrated use of real world examples.